2019
DOI: 10.1186/s12974-019-1615-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of n-6 polyunsaturated fatty acid deprivation on the inflammatory gene response to lipopolysaccharide in the mouse hippocampus

Abstract: BackgroundNeuroinflammation is thought to contribute to psychiatric and neurological disorders such as major depression and Alzheimer’s disease (AD). N-6 polyunsaturated fatty acids (PUFA) and molecules derived from them, including linoleic acid- and arachidonic acid-derived lipid mediators, are known to have pro-inflammatory properties in the periphery; however, this has yet to be tested in the brain. Lowering the consumption of n-6 PUFA is associated with a decreased risk of depression and AD in human observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…PUFAs are classified as n-3 and n-6 PUFAs according to the location of the double bonds. The derivates from n-3 PUFAs have anti-inflammatory and immunomodulatory properties (Weylandt et al, 2012;Calder, 2015), whereas those from n-6 PUFAs are generally known to have pro-inflammatory effects (Alashmali et al, 2019). Some specific n-6 PUFA changes related to SLE were discovered in this study.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…PUFAs are classified as n-3 and n-6 PUFAs according to the location of the double bonds. The derivates from n-3 PUFAs have anti-inflammatory and immunomodulatory properties (Weylandt et al, 2012;Calder, 2015), whereas those from n-6 PUFAs are generally known to have pro-inflammatory effects (Alashmali et al, 2019). Some specific n-6 PUFA changes related to SLE were discovered in this study.…”
Section: Discussionmentioning
confidence: 63%
“…Some species of FA can affect the inflammatory state of the body. For example, linoleic acid and arachidonic acid (AA) have pro-inflammatory effects (Alashmali et al, 2019), while docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) have anti-inflammatory and immunomodulatory properties (Weylandt et al, 2012;Calder, 2015). Previous studies have found that abnormal FA levels are associated with insulin resistance and atherosclerosis (Lepretti et al, 2018;Steffen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is commonly recognized that n-6 PUFA has pro-in ammatory functions as prostaglandin and leukotriene precursors, n-6 PUFA can also be converted into anti-in ammatory mediators or modulate the gene expression of the pro-in ammatory cytokine to exert anti-in ammatory effects. Alashmali et al reported that adequate dietary n-6 PUFA intake restored hippocampal in ammation cytokine gene expression caused by intra-cerebroventricular lipopolysaccharide (LPS) injection [53]. We, therefore, speculate that the AD-like pathology in APP/PS1 mice might have caused hyperactivated neuroin ammation in the brain, which could be antagonized by the treatment with HFD.…”
Section: Discussionmentioning
confidence: 84%
“…The number of astrocytes was positively correlated with the expression of Mfs2a in the brain (Tiwary et al, 2018). Alashmali et al (2019) found that the upregulation of Mfsd2a in mice adequately fed with N-6 PUFA is possibly due to the high presence of astrocytes, maintaining Mfsd2a expression in the brain and controlling BBB homeostasis. In the future, studies on Mfsd2a-knockout mice are expected to clarify the mechanism by which N-6 PUFA affects the expression of Mfsd2a in the brain.…”
Section: Alzheimer's Diseasementioning
confidence: 86%